Extensive somatic L1 retrotransposition in colorectal tumors - Solyom, Szilvia; Ewing, Adam D.; Rahrmann, Eric P.; Doucet, Tara; Nelson, Heather H.; Burns, Michael B.; Harris, Reuben S.; Sigmon, David F.; Casella, Alex; Erlanger, Bracha; Wheelan, Sarah; Upton, Kyle R.; et al. (Genome Research, 2012)
L1 retrotransposons comprise 17% of the human genome and are its only autonomous mobile elements. Although L1-induced insertional mutagenesis causes Mendelian disease, their mutagenic load in cancer has been elusive. Using L1-targeted resequencing of 16 colorectal tumor and matched normal DNAs, we found that certain cancers were excessively mutagenized by human-specific L1s, while no verifiable insertions were present in normal tissues. We confirmed de novo L1 insertions in malignancy by both validating and sequencing 69/107 tumor-specific insertions and retrieving both 5′ and 3′ junctions for 35. In contrast to germline polymorphic L1s, all insertions were severely 5′ truncated. Validated insertion numbers varied from up to 17 in some tumors to none in three others, and correlated with the age of the patients. Numerous genes with a role in tumorigenesis were targeted, including ODZ3, ROBO2, PTPRM, PCM1, and CDH11. Thus, somatic retrotransposition may play an etiologic role in colorectal cancer.
10.1101/gr.145235.112